PENGEMBANGAN MEDIA FLASH PADA PENGENALAN KOSAKATA DALAM CERITA RAKYAT JEPANG â€œSARU KANI KASSENâ€ - CINTIAPUTRI, RESTY (HIKARI, 2020)
Abstract Literature is a familiar thing for language learners. Likewise for Japanese language learners, studying a literary work can increase vocabulary to understand a work. However, literary learning is not taught at school. Teaching literature is important to teach, to support language skills. One of Japanese literary works is folklore. The saru kani kassen folklore is one of the most well-known stories in Japan. Flash media are media that contain animated "Saru kani Kassen" folklore accompanied by hiragana letters, romaji and Indonesian translations. This media also contains a collection of vocabulary and practice questions. In this study flash media was developed to help students learn new Japanese vocabulary in the "Saru Kani Kassen" folklore. The purpose of this study is to determine the feasibility and response of students to Flash media. This research is the development of a research based on Sugiyonos development model. This research was conducted on students of Labschool Unesa High School class XI. The results of the study are disclosed below: 1. From the Flash media feasibility test the results obtained are, 84% obtained from material experts. While from media experts the results were 97%. Based on these results, flash media gets very good and decent results. 2. Based on the analysis of student questionnaire responses, Flash media received very good responses with a percentage of 82.5%. With these results, this flash media is appropriate to be used to introduce Japanese vocabulary. However, to make a media that really senpurnya, still needed improvement. Keywords: development, flash media, vocabulary, Saru Kani Kassen folklore ?? ??????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ?????????????????2015:42????????????????????????SMA Labschool Unesa????????????????????????????????????? 1. ???????????????????????84????????????97???????????????????????????????????? 2. ????82,5?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ???????????????????????????????????